Globalism/localism at work - Beukema, Lena Margaretha, 1954-; Carrillo V., Jorge (Carrillo Viveros) (Research in the sociology of work, 2004)
In this volume the focus is on the interrelations of the global and the local in their consequences for work. The process of restructuring of work is analyzed as an ongoing, locally situated process in which actors within work organizations play an important role. Nevertheless, when taking the context of work organizations into account, the increasing importance of the global on the local processes is obvious. Local practices keep their central importance, but the global doesn't function only as a context for the local anymore but forms more and more a practice of itself in which an increasing number of actors play their part.As we can see on the World Wide Web, people and firms are both emitters and receptors and act on the local and global level at the same time. Local diversity in a world with increasing interdependencies is shown in a number of contributions from different parts of the world. These contributions are clustered around two main themes: Labor markets in global and local scenarios - From industry to services; Global industries - Restructuring and local jobs. The many case studies presented shed light to the diversity that occurs in different local situations.